Low‐voltage and ion‐free‐reverse‐migration electrically regenerated mixed‐bed ion exchange for MEG desalination. Issue 6 (11th August 2020) - He, San; Zhang, Xiaozhuo; Yang, Wen; Zhao, Zhichao
Abstract: An improved electrical regeneration method of ion exchange was proposed to enhance the feasibility of applying ion exchange for mono‐ethylene glycol (MEG) desalination and simplify the existing MEG regeneration process in deepwater gas fields. Compared with the latest electrical regeneration process named membrane‐free electrodeionization (MFEDI), this method required lower voltage, did not consume high purity water, and eliminated ion backward migration in principle. These improvements were achieved by changing the electric field direction and the flow direction from parallel in MFEDI to perpendicular during ion exchange regeneration step. In this work, a pair of commercial ruthenium oxide‐coated titanium electrodes was installed on both sides of the cuboid experimental setup. The mixed resins consisting of strong‐base and weak‐acid resins were filled between the electrodes. In water flow and direct current electric field, the resins were regenerated successfully. The feasibility of efficient regeneration with high conductivity feed water (3–200 μS/cm) was verified. After regeneration of the resin bed for 1 h at a voltage lower than 73 V, 33.83% of NaCl in 5.16 bed volume (BV) simulated rich MEG liquid was removed. After 15 cycles of repeated operation, the performance of the resins remained stable. These results provide the possibility to reclaim MEG in deepwater gas fields through a simpler method.